2002
DOI: 10.1007/s00420-001-0294-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychosocial work characteristics and fatigue and psychological distress

Abstract: The study provides strong support for associations between psychosocial work characteristics and fatigue in men and women, even after adjustment for psychological distress. Moreover, it suggests some differential effects of psychosocial work characteristics on fatigue and psychological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
2
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 24 publications
10
101
2
4
Order By: Relevance
“…Career factors include the following: underestimation of performance by supervisors; lack of opportunities to utilize abilities; lack of future job prospects; and insecurity regarding job prospects owing to health. Prior studies have also addressed the relationship between prolonged fatigue and qualitative and quantitative workload 15,22) . It came as no surprise to find similar trends among teachers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Career factors include the following: underestimation of performance by supervisors; lack of opportunities to utilize abilities; lack of future job prospects; and insecurity regarding job prospects owing to health. Prior studies have also addressed the relationship between prolonged fatigue and qualitative and quantitative workload 15,22) . It came as no surprise to find similar trends among teachers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed the findings of Vermeulen and Mustard (2000) 27) , who reported that supervisor/co-worker support was significantly related to low perceived work stressors and low psychological distress. Bültman et al (2002) 28) , in the Maastrict Cohort Study, found that conflict with supervisors was significantly associated with psychological distress 29) reported that relationship with supervisor and co-workers was a significant predictive factor for level of psychological strain among Korean factory workers. The findings also indicated that workers with high job insecurity were 2.25 times more likely to develop job strain than those with low job insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged fatigue is associated with impairments comparable to chronic medical conditions, and may affect the individual's performance and functioning in the occupational as well as home setting (BÜLTMANN et al 2002;BÜLTMANN et al 2003;JONG et al 2003;HULST et al 2006;JANSSEN et al 2003). Mental fatigue is defi ned and operationalised in various ways, for example in terms of increased sleepiness, reduced alertness, reduction in motivation, reduction in activity, and reduction in concentration (JANSSEN et al 2003;TARIS et al 2006).…”
Section: Mental Fatiguementioning
confidence: 99%
“…Consequently, it may have a huge impact on an individuals' well-being and on the school organization as a whole (JEPSON & FORREST 2006). High levels of occupational stress, when experienced in the long term, can lead to a state of burnout (MASLACH et al 2001), exhaustion, psychosomatic complaints, and lack of work engagement (BÜLTMANN et al 2002).…”
Section: Introductionmentioning
confidence: 99%